Impact of Clinical Pharmacists in Inflammatory Bowel Disease Centers During the COVID-19 Pandemic. (20th September 2020) - Bhat, Shubha; Farraye, Francis A.; Moss, Alan C.
Abstract : INTRODUCTION: To characterize the clinical pharmacists' impact on caring for patients with inflammatory bowel disease during COVID-19. METHODS: A clinical pharmacist's encounters between March 17 and April 14, 2020, were audited to determine encounter frequency and indication. RESULTS: The clinical pharmacist addressed COVID-19 and inflammatory bowel disease treatment concerns with 140 patients, conducted 34 medication education and monitoring visits, reviewed 141 patients' charts and helped rescheduled 18 patients who missed their biologic infusion, transitioned 12 patients to home infusions, and assisted 5 patients with medication access. DISCUSSION: Clinical pharmacists embedded in gastroenterology practices permit for continued optimal patient care during a pandemic.